2016
DOI: 10.1007/s40136-016-0121-5
|View full text |Cite
|
Sign up to set email alerts
|

Reflux and Voice Disorders: Have We Established Causality?

Abstract: A trend of attributing abnormal voice changes to reflux has gained momentum among medical professionals over the last few decades. Evidence supporting the connection between reflux and voice and the use of anti-reflux medication in patients with dysphonia is conflicting and deserves careful examination. In the current health care environment, it is important that medical decisions be based on science rather than anecdote and practice patterns. The goal of this review is to investigate the evidence linking refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 70 publications
0
19
0
1
Order By: Relevance
“…LPRD refers to reflux of gastric contents into the laryngopharynx of sufficient severity presumed to cause a constellation of symptoms including throat-clearing, cough, globus sensation, and hoarseness. 8 Because a reliable, validated gold standard for LPRD does not exist, patient-reported symptoms are often used as a surrogate for LPRD diagnosis. For the potential diagnosis of LPRD, the RSI is the most commonly accepted patient-reported outcome measure (PROM).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LPRD refers to reflux of gastric contents into the laryngopharynx of sufficient severity presumed to cause a constellation of symptoms including throat-clearing, cough, globus sensation, and hoarseness. 8 Because a reliable, validated gold standard for LPRD does not exist, patient-reported symptoms are often used as a surrogate for LPRD diagnosis. For the potential diagnosis of LPRD, the RSI is the most commonly accepted patient-reported outcome measure (PROM).…”
Section: Discussionmentioning
confidence: 99%
“…The RSI assesses nine symptoms that span both voice and traditional gastroesophageal reflux symptoms and includes items such as heartburn, cough, globus, and voice dysfunction . Although LPRD is a physiologically plausible explanation for dysphonia, randomized controlled trials assessing the utility of antireflux therapy to improve voice outcomes have demonstrated mixed results . Moreover, studies have demonstrated that non‐LPRD cases of dysphonia demonstrate elevated RSI scores and that voice therapy may improve RSI scores in LPRD patients when used both with and without a PPI .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first insight that can be found in literature, concerning the possible involvement of ENT anatomical structures in the reflux pathology, goes back to 1903; in fact, Coffin speculated "gas reflux from the stomach" as well as the "hyper-acidity" could be considered responsible for hoarseness and back rhinorrhea [1][2][3][4]. Starting from the '80s, besides the relatively "old" knowledge of GED, a new concept arose; it proposed LPR could have been caused by "acid vapors" action, coming from the stomach.…”
Section: Introductionmentioning
confidence: 99%
“…Starting from the '80s, besides the relatively "old" knowledge of GED, a new concept arose; it proposed LPR could have been caused by "acid vapors" action, coming from the stomach. Those vapors, after being in contact with the esophageal mucosa and having passed through the Upper Esophageal Sphincter (UES), reach the upper respiratory tract: larynx, laryngopharynx, and finally the nose sinus area [3,5,18] and the middle ear through the auditory tubes [1,6,7].…”
Section: Introductionmentioning
confidence: 99%